Poročilo z Dnevov Maksa Pleteršnika: Izzivi sodobnega slovenskega slovaropisja: Pišece, 13. in 14. 9. 2010 - Benko, Anja (Slavia Centralis, 2020)
The author presented the traditional scientific meeting Days of Max Pleteršnik on the topic Challenges of contemporary Slovenian lexicography, which took place on 13 and 14 September 2010 in Pišece.